Analisis Faktor-Faktor yang Mempengaruhi Status Kesehatan pada Pasien Hemodialisis di Rumah Sakit Medika BSD - Nurbaiti, Syifa; Mulyani, Erry Yudhya; Sa’pang, Mertien; Wahyuni, Yulia; Novianti, Anugrah (Universitas Muhammadiyah Semarang, 2022)
Chronic Kidney Disease (CKD) is a condition where the kidney(s) are damaged which is marked by the glomerular filtration rate<15mL/min/1.73m². Reports from IndonesianRenal Registry revealed that new patients undergoing hemodialysis in the Indonesian areincreasing every year. This study aims to see the health status of hemodialysis patients atMedika Hospital BSD. The design used was descriptive observational in November 2019 -February 2020, with cross sectional research design. The sampling method uses NonProbability Sampling, total samples taken was 46 respondent with age ratio >18 years to <60years old. The results showed 56.5% ureum levels >150 mg/dL, 76.1% hemoglobin levels ≤10g/dL, 71.7% malnutrition nutritional status (DMS score = >7), and 84.8% of the respondenthas bad health status. Keywords: Ureum levels, Hemoglobin levels, Dialysis Malnutrition Score (DMS), HealthStatus